An atomistic study of the influence of carbon on the core structure of screw dislocation in BCC Fe and its consequences on non-Schmid behavior. (June 2022) - Sarangi, Soumya Sourav; Kanjarla, Anand K.
Abstract: In the present work, we report on the effect of introducing carbon atom in the core of the screw dislocations in body centered iron (Fe) using classical interatomic potentials available in open literature. Reconstruction of dislocation core from easy to hard core configuration is observed irrespective of the initial position of the carbon atom, which eventually settles in the dislocation core occupying the prismatic sites formed by the rows of Fe atoms in hard core. Loading is carried out parallel and perpendicular to the Burgers vector to understand the effect of carbon on the non-Schmid characteristics of the slip. Twinning–antitwinning (T/AT) asymmetry of CRSS is observed when the dislocation core symmetry of the easy core configuration is retained after the core reconstruction occurs. The CRSS of dislocation in both easy and hard core configuration is sensitive to the loading conditions. The asymmetry in CRSS and choice of glide planes are correlated with the dislocation core spreading onto the {1 1 0} planes in the 〈 1 1 1 〉 zone under the influence of the applied loads. Graphical abstract: Highlights: Dislocation–carbon interaction is evaluated using classical interatomic potentials. Reconstruction of core occurs from easy to hard core configuration. T/AT asymmetry of CRSS is only observed for hard core with non-degenerate structure. Easy core and hard core configurations respond differently to applied loads. CRSS values for systems are correlated with the dislocation core structures.